Associations of bisphenol F and S, as substitutes for bisphenol A, with cardiovascular disease in American adults. Issue 4 (11th October 2022) - Lu, Yuan; Chen, Shaoxi; Jin, Hongfeng; Tang, Lijiang; Xia, Ming
Abstract: Bisphenol A (BPA) exposure may be positively associated with cardiovascular disease (CVD). For more than a past decade, exposure to bisphenol F (BPF) and bisphenol S (BPS), as substitutes for BPA, has gradually increased in the population. Whether BPF and BPS exposure are associated with CVD remains unclear. We used data from the United States National Health and Nutrition Examination Survey (NHANES) from 2013 to 2016. A total of 3, 502 participants, including 368 with CVD, were enrolled in the final analysis. Associations of BPA, BPF and BPS with CVD were determined using multivariate logistic regression analysis. The highest level of urinary BPA (≥2.5 ng/ml) was significantly associated with a higher CVD prevalence (odds ratio [OR], 1.58; 95% confidence interval [CI], 1.08–2.3) among all participants in the quartile analysis. In stratified analyses, the highest level of urinary BPA was positively associated with CVD prevalence in males (1.86, 1.1–3.13) and the elderly population (≥60 years old) (1.89, 1.2–2.97). Higher levels of urinary BPF were positively associated with CVD prevalence in females (Q2: 1.81, 1.03–3.18; Q4: 1.73, 1.07–2.79) and in the elderly population (Q3: 1.7, 1.16–2.48). No associations were found between urinary BPS levels and CVD, regardless of whether the participants were stratified by age or sex. In conclusion, exposure to BPA or BPF was positively correlated with CVD prevalence, but an association was not found for exposure to BPS. BPF may not be as safe as assumed for human health. Abstract : Bisphenol A (BPA) exposure may be positively associated with cardiovascular disease (CVD). Whether there are associations between exposure to BPF and BPS as substitutes for BPA and CVD remains unclear. We analyzed the associations of exposure to BPA, BPF and BPS with CVD by using data from the NHANES from 2013 to 2016. The study showed that exposure to BPA or BPF was positively correlated with CVD prevalence, but exposure to BPS was not.